Poor science meets political neglect: Land use changes of high conservation value forests in Indonesia - Nurprabowo, Arnanto; Awang, San Afri; Hardwinarto, Sigit; Dharmawan, Budi; Daulay, Muhammad Haidar; Maryudi, Ahmad (Forestry Faculty, Universitas Hasanuddin, 2021)
Forest land allocation and use in Indonesia have been politically contested and characterized by poor data and competing interests of different institutions. This study analyzes the process of integrating scientific findings in policymaking about land use and changes. The focus is on the processes related to the changes of Highly Important Forest Zones with Strategic Values (Dampak Penting Cakupan Luas dan bernilai Strategis/DPCLS). DPCLS forests are unique as any changes require approval from the parliament to complement the processes at the Ministry of Environment and Forestry and must be based on rigorous scientific evaluation. This study uses the case of Riau Islands (Kepri) Province, previously part of Riau Province, which to date is one of only two Indonesian provinces yet to accept the forest zonings of the Ministry. The province’s strategic positions as exclusive economic and free trade zones make it further interesting in terms of land allocation as land becomes increasingly valuable for other uses. This paper specifically asks how the scientific investigation on the potential land use changes were conducted, how reliable the discoveries are, and how they were utilized in multiple steps at different institutions from the proposal evaluations to the approval stages. Our research indicates that scientific findings have rarely been integrated in policy making regarding DPCLS forests in Kepri Province. In addition, the scientific findings are weak; the institution producing them is heavily dominated by government officials and paid consultants/ experts. The scientific body was only established to fulfill the formal processes required by the regulatory frameworks. Proposals and decisions on the changes of DPCLS forests in Kepri Province are more characterized by political considerations. The “scientific findings” of the current land use in Kepri Province is used as a political commodity (or commodities) to support the interests of actors.